Joint Interpolation and Representation Learning for Irregularly Sampled Satellite-Derived Geophysical Fields - Fablet, Ronan; Beauchamp, Maxime; Drumetz, Lucas; Rousseau, François (Frontiers in Applied Mathematics and Statistics, 2021)
Earth observation satellite missions provide invaluable global observations of geophysical processes in play in the atmosphere and the oceans. Due to sensor technologies (e.g., infrared satelitte sensors), atmospheric conditions (e.g., clouds, heavy rains) and satellite orbits (e.g. polar-orbiting satellites), satellite-derived observations often involve irregular space-time sampling patterns and large missing data rates. Given the current development of learning-based schemes for earth observation, the question naturally arises whether one might learn some representation of the underlying processes as well as solve interpolation issues directly from these observation datasets. In this paper, we address these issues and introduce an end-to-end neural-network learning scheme, which relies on an energy-based formulation of the interpolation problem. This scheme investigates different learning-based priors for the underlying geophysical of interest. The end-to-end learning procedure jointly solves the interpolation and the training of the considered priors. Through different case-studies, including observing system simulation experiments for sea surface geophysical fields, we demonstrate the relevance of the proposed framework compared with optimal interpolation and other state-of-the-art data-driven schemes.